PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fitri, Wanda Febilia; Retnaningdiah, Dian (Program Studi Manajemen, 2022)
In the current era of globalization, all industrial companies will develop rapidly with the advantages created by each company. In this case, the alternative is usually used by the company to maintain its advantage, namely by investing in the capital market. In the Indonesian Stock Exchange there are various options for investing; one of which is in the health sub-sector.The health sub-sectoris included in the trading and investment category on the Indonesia Stock Exchange which plays an important role in the Indonesian economy in investment. This study aims to determine the effect of Return on Assets, Earning Per Share,and Price to BookValue on stock prices in health sub-sector companies listed on the Indonesian Stock Exchange. This study applied the Purposive Sampling method in sampling. The data used secondary data collected using the data documentation method. The results of this study can be concluded that (1) Return on Assets (X1) significantly affects stock prices; (2) Earning Per Share (X2) significantly affects stock prices; (3) and Price to Book Value(X3) has no significant effect on stock prices; (4) Return on Assets (ROA), Earning Per Share (EPS), and Price to Book Value (PBV) together have an effect on stockprices.